Pendidikan Matematika Kritis (Sebuah Kajian Filosofis dan Pedagogis) - Ade Alimah (Universitas Islam Negeri (UIN) Mataram, 2013)
Critical mathematics education is an approach of mathematics contextualization in which its learners can develop mathematical knowing, technological knowing and reflextive knowing. Mathematical knowing is skills developed in traditional teaching; technological knowing can be associated with a competence in mathematical model building; and reflective knowing can be seen as a competence in evaluating applications of mathematics. Critical mathematics education is intended to raise students’ critical consciousness against prevailing social inequalities that in turn they can apply mathematics in development of social justice. Instead of traditional banking pedagogy, critical mathematics education requires critical pedagogy emphasizing problem posing learning and dialogical relation. Critical pedagogy can be implemented through mathematics project work based on problem orientation, students’ participation, interdisciplinary approach, exemplarity, authentic and formative assessment, and activity organization. Despite high-stakes Indonesian education system, it seems that critical mathematics education is relevant to 2013 curriculum that highlights the development of learners’ attitudes and behaviors, knowledge, as well as skills.